DIAGNOSIS AND MANAGEMENT OF INFANTILE HEMANGIOMA - Suryaguna, I Made Sakta (E-Jurnal Medika Udayana; vol 2 no 12 (2013):e-jurnal medika udayana, 2013)
1024x768 Hemangiomas are benign neoplasms composed of proliverative and hyperplastic vascular endothelium with characteristic rapid growth of initial phase followed by involution phase or regression . Hemangiomas are the most common benign vascular tumor in the naonatus . The pathogenesis of hemangiomas still can not be explained with certainty although there is some suspicion about the cause. Clinical symptoms and diagnosis of hemangioma can be seen by the growth phase of hemangioma . Most hemangiomas will regress spontaneously , but treatment as early as possible with the appropriate modality can provide better results , especially with the new therapeutic modalities such promising class of beta blockers . Normal 0 false false false EN-US X-NONE X-NONE /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: Hemangioma, Infantile, Diagnosis, Treatment